PERANCANGAN ALAT BANTU KERJA DENGAN MENGGUNAKAN METODE ANTROPOMETRI DAN MATERIAL SELECTION PADA INDUSTRI SEPATU - Ratna Dewi Anjani; Asep Erik Nugraha; Rianita Puspa Sari; Deri Teguh Santoso (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2021)
MSMEs of shoes and sandals producers in Cibaduyut centers in the process of work that is carried out continuously, are known to have a high enough risk, namely in the process of installing sole. The sole installation process in the Home Industry is still using modest work facilities. Besides this sole installation is often done not on the table but on the thigh of the worker, this is very dangerous for the worker because he has a high enough risk of accidents, so that workers become uncomfortable at work. The purpose of this research is to design a working aid in the form of a workbench at the sole of shoe installation station with material selection so that the worker's body position becomes safer, more comfortable and healthier so as to reduce the risk of work accidents due to unfavorable work positions and will increase work productivity. The method used in this study, is an anthropometric method to measure the level of risk of danger from the worker's posture that is using the RULA (Rapid Upper Limb Assessment) method. This calculation is only done at the sole station. Furthermore, using the results of the RULA method, a working tool design in the form of a sole of shoe mounting table can be designed using an appropriate software based on raw material selection, as well as the principles of mechanics and ergonomics.